Study on model of game for great performance in volleyball and elements of progress - Cojocaru, A. M.; Cojocaru, M. (Science, Movement & Health, 2013)
Need knowledge of the game and the current model of development trends, is an essential requirement for specialist must harmonize and design training content, depending on the essential elements of the game's top teams worldwide value and in accordance with the actual availability of potential biomotric their technical and tactical players and teams. In this context, the analysis of the current game at peak performance teams participating in qualifying tournaments and world championships, with implications for the future of game design, player and training, we draw several trends, of which we speak dedicated team of formula is 5T 1 R, are launched into a very low number of changes to the reserve players (except libero player) or tactical play aspect that is designed to the smallest detail, missing improvisations time particularly unprepared Hypothesis. We can talk about specialization player positions and areas of maximum efficiency for attack, block and retrieval, which is done on a broad background of training in the majors, all with a special motric labor, with nervous consumption. Current level of play, the expression realization of options, which gave endorsement practice efficiency and allowed generalization beyond the strict context of the team. Method. For comparative analyzes of various parameters of models of game and player characteristics, we proceeded to use methodological tools that experts recommend it for this purpose. At the basis of the work, stays a rich analysis of information material, studied and consulted and their views and experiences shared by many specialists and technicians, with extensive work in performance volleyball players. Discussion. Modernization is a complex process of reconsideration, the revaluation of all that still proves valuable performance and introducing innovative elements with value and performance validated by practice .. Modernization is not a simple act, but it is a complex and continuously interacting with many implications between all elements of the structural and functional basis of democratic institutions and coach-athlete relationship, and to redefine the objectives, content modification training and game adequacy competitive system methodologies and organizational framework performance. Conclusions. Putting in accordance with current and future requirements of performance volleyball players, volleyball Romanian require the need for continuous improvement and modernization, not by simple additions or selection of knowledge, but through a restructuring of the entire system performance, the position of systems theory, which and gives a high degree of efficiency